UJI FORMULA BIOFUNGISIDA TABLET BERBAHAN AKTIF KONSORSIUM Trichoderma virens ENDOFIT DAN MIKORIZA INDIGENOUS TERHADAP PENYAKIT JAP PADA BIBIT KARET - Lestari Magdalena; Fifi Puspita; Muhammad Ali (DINAMIKA PERTANIAN, 2021)
The objective of this research is to determine the effect of biofungicide tablets with active ingredient of the consortium consisted Trichoderma virens endophyte and mycorrhiza indigenous and to get the best formula to control the JAP disease on rubber plant. The research was carried out experimentally by using a completely randomized design (RAL), consisting of 6 treatments and 4 replications in order to obtain 24 experimental units. Each experimental unit consisted of two seeds, so there were 48 rubber seeds. The treatments seed were: F1 (15 ml T. virens endophyte), F2 (15 gr inokulan mychorrhiza), F3 (15 ml T. virens endophyte + 15 gr inokulan mychorrhiza + 100 gr palm fronds powder + 25 gr zeolite + 25 gr tapioca powder), F4 (15 ml T. virens endophyte + 15 gr inokulan mychorrhiza + 100 gr sago powder + 25 gr sago dregs + 25 gr tapioca powder), F5 (15 gr inokulan mychorrhiza + 100 gr solid + 25 gr zeolite + 25 gr tapioca powder) and F6 (15 ml T. virens endophyte + 100 gr cocoa shells powder + 25 gr sago dregs + 25 gr tapioca powder). Parameter observerd were initial symptoms on seedlings, intensity of disease, addition of plant height, stem diameter, and weight of dry seedlings. The data obtained were analyzed for variance followed by further tests of honest real difference (BNJ) at the 5% level. The results indicated that F3 (15 ml T. virens endophyte + 15 gr inokulan mychorrhiza + 100 gr palm fronds powder + 25 gr zeolite + 25 gr tapioca powder) was the best formula in controlling JAP with initial symptoms of infection of 24,50 days with the seedling height was 69,46 cm, stem diameter and dry weight were 6,60 cm and 103,62 gr respectively.